Research : a science partner journal - Science Partner Journals Program; American Association for the Advancement of Science; Zhongguo ke xue ji shu xie hui (American Association for the Advancement of Science, 2018)
Publishes innovative, wide-ranging research in life sciences, physical sciences, engineering and applied science.
Keywords: Research : Periodicals; Research; Engineering; Biological Science Disciplines